CONSERVATION OF THREATENED PLANT SPECIES IN DONG VAN KARST PLATEAU GEOPARK, HA GIANG PROVINCE - Van Sam, Hoang; Van Dung, Phan; Thuy Linh, Dao; Thi Hue Phuong, Dan; Van Dien, Pham; Tuan Cuong, Nguyen (Journal of Forestry Science and Technology, 2016)
This paper provides information regarding threatened plant species in Dong Van Karst Plateau Geopark, Ha Giang province. This study aims to determine the composition, conservation status and propose solutions to protect threatened plant species in the geopark. Based on observations and measurements of general characters, results indicate that there are 13 threatened plant species distributed in Dong Van, belonging to 10 families. There are 11 species listed in Viet Nam Red List (2007), five species listed in IUCN (2015), and five species listed in Decree 32/2006/NDCP. Most of the species are distribute from 1500m to 1800m above sea level. Only three species are distributed between 1000m - 1300m. This research also provides information of morphologial and ecological characteristics of the three endangered species Taxus chinensis (Pilg.) Rehder, Pinus kwangtungensis Chun ex Tsiang and Tsuga chinensis ( Franch) Pritzel ex Diels.